Numerical Investigation of Fluid Flow Instabilities in Pore-scale with Heterogeneities in Permeability and Wettability (Rudarsko-geološko-naftni zbornik, 2021)
Quadrant geometry with permeability and wettability contrast occurs in different events, such as faults, wellbore damage, and perforation zones. In these events, understanding the dynamics of immiscible fluid displacement is vital for enhanced oil recovery. Fluid flow studies showed that viscous fingering occurs due to viscous instabilities that depend on the mobility of fluids and capillary forces. Besides, the porous domain heterogeneity is also effective on the formation of fingering. So, the purpose of the current research is to numerically investigate the effect of heterogeneity in wettability and permeability, and flow properties in Saffmann-Taylor instabilities. Numerical simulations with different flow rates in the permeability contrast model illustrated the nodal crossflow, growth of viscous fingering in the nodal part, and bypass flow in the second zone. In the wettability contrast model, a capillary fingering pattern is observed and fluid patches are isolated because of capillary force and the end effects are trapped within the quadrant. Moreover, the consequences of wettability on apparent wettability that alters the fluid-front pattern and displacement efficiency are shown.